The Effect of Profitability on Stock Prices with Shariah Corporate Social Responsibility as a Moderating Variable (A Study of Shariah Banks Listed on the Indonesia Stock Exchange) - Putri Indah; Erniyati Caronge; Halim Usman (LP2M IAIN Palopo, 2026)
This research aims to analyze Islamic banks listed on the Indonesia Stock Exchange (IDX) and their stock prices in relation to profitability and Shariah Corporate Social Responsibility (Shariah CSR). Profitability affects stock prices significantly, with Shariah CSR acting as a moderator, according to the study hypothesis. This study employs a quantitative approach using secondary data obtained from financial statements and annual reports. Profitability is proxied by Return on Assets (ROA), stock prices are proxied by market prices, and Shariah CSR is measured using the Islamic Social Reporting (ISR) index. Data analysis is conducted using Moderated Regression Analysis (MRA). The results indicate that profitability has a significant effect on stock prices and that Shariah CSR is proven to be a significant moderating variable. The implications of this study provide practical contributions for Islamic bank management in improving financial performance and the quality of Shariah CSR disclosure, as well as empirical contributions for investors in making investment decisions in the Islamic capital market.